The characterisation for South African taxation purposes of gains and losses arising from the use of equity financial derivative instruments - Smith, Stephen Eugene (Department of Commercial Law, 2021)
The use of financial derivative instruments has outpaced the development of a comprehensive tax policy framework for these instruments in South Africa. Income character determination relies on common law principles which provide limited certainty within the context of modern portfolio management. How the courts will approach character determination for financial derivative instruments within investment portfolios is uncertain. This thesis considers applicable tax legislation and case law in three common law jurisdictions. The United States, the United Kingdom and Australia provide insight into the difficulties associated with formulating legislation in the light of rapid market innovation. The detailed tax code of the United States has proved a less than satisfactory policy approach and the courts have struggled with doctrines of interpretation. Australia and the United Kingdom have followed accounting principles. Simplifying proxies are used in this thesis to help disentangle the analysis from the varied and complex ways in which derivatives can be used in financial transactions. Only equity derivatives are considered within the context of regulated investment portfolios. Insolvency case law following the filing for bankruptcy by Lehman Brothers Holdings Incorporated in 2008 provides authority with which to analyse the nature of standardised derivative contracts used in the markets and the rights therefrom as ‘property'. The researcher argues per Smalberger JA in CIR v Pick ‘n Pay Employee Share Purchase Trust 1992 (4) SA 39 (A) that, ‘transactions involving shares do not differ from transactions in respect of any other property and the capital or revenue nature of a receipt is determined in the same way whether one is dealing with land or shares'. A definition is proposed to incorporate legal attributes of these instruments highlighted in the literature, and interpretive guidance issued by Her Majesty's Revenue and Customs in the United Kingdom is supported for adoption as policy principles aligned with our own common law. There can be no context distinct from the general concepts of law specific to derivatives. Continuity and coherency within a long tradition of case law on capital and revenue characterisation should be maintained and a policy framework developed from this premise.